2021
DOI: 10.1080/13811118.2021.1938321
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and Self-Harm Risk Assessment: A Systematic Review of Prospective Research

Abstract: Objective: Suicide and self-harm are widespread yet underreported. Risk assessment is key to effective self-harm and suicide prevention and management. There is contradicting evidence regarding the effectiveness of risk assessment tools in predicting self-harm and suicide risk. This systematic review examines the effect of risk assessment strategies on predicting suicide and self-harm outcomes among adult healthcare service users. Method: Electronic and gray literature databases were searched for prospective r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 49 publications
0
19
0
1
Order By: Relevance
“…Despite these intervention efforts, the issue remains significant and is further complicated by a distinct lack of literature and understanding regarding drivers of suicidal trajectories for this population. While there is largely widespread agreement regarding the limited predictive validity of suicide from a structured risk assessment, there is acceptance of early stages of the suicidal trajectory, namely suicidal ideation, as a useful identifier of future suicide risk [ 7 , 8 , 9 , 10 , 11 ]. As a result, scholars suggest knowledge and mitigation of the drivers of suicidal ideation, independent from suicidal behaviours and attempts, is a key component in effective suicide prevention [ 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these intervention efforts, the issue remains significant and is further complicated by a distinct lack of literature and understanding regarding drivers of suicidal trajectories for this population. While there is largely widespread agreement regarding the limited predictive validity of suicide from a structured risk assessment, there is acceptance of early stages of the suicidal trajectory, namely suicidal ideation, as a useful identifier of future suicide risk [ 7 , 8 , 9 , 10 , 11 ]. As a result, scholars suggest knowledge and mitigation of the drivers of suicidal ideation, independent from suicidal behaviours and attempts, is a key component in effective suicide prevention [ 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A brief risk assessment asking about known psychosocial risk factors 20 30 can reduce the risk of false positives and enhance disposition planning. Although screening tools show good predictive validity for future suicide-related behaviour, another commonly cited limitation is the lack of data related to predictive validity for death by suicide 31. Further research is needed to determine if universal screening can reduce rising suicide rates.…”
Section: Discussionmentioning
confidence: 99%
“…This limited control was further exacerbated by ED staffs' limited confidence in their ability to stratify risk, which is not surprising given the complexity of suicide presentations. A 2021 systematic review of 21 studies showed that no one suicide risk assessment tool, including clinical assessment, could accurately predict the risk of future suicide behavior ( 41 ). In contrast, there is some evidence to show that greater exposure to help seekers may improve accuracy of assessed suicide risk ( 16 ), yet ED staff in this study often chose to relinquish this responsibility and defer to other ED mental health staff whom they believed were best placed to make assessment, treatment, and discharge decisions.…”
Section: Discussionmentioning
confidence: 99%